2022
DOI: 10.1080/02602938.2022.2041545
|View full text |Cite
|
Sign up to set email alerts
|

Talking during a test?! Embracing mobile instant messaging during assessment

Abstract: This study reports on the incorporation of mobile instant messaging (MIM) in assessments, as a collaborative learning tool, to enable students to socially construct knowledge and develop their collaborative problem solving competence, while being assessed individually. In particular, this study explores: what is the extent and timing of students' use of MIM to communicate with other students while being assessed individually? What communicative activities are evident in the content of students' MIM communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…As mobile technologies gain popularity among students, many studies have investigated the effectiveness of integrating these technologies into the learning activities. A study by van Rensburg et al (2022) reported the positive impact of using mobile technologies for learning in terms of increasing learning opportunities for students. Assessment as part of learning activities has become one of the domains that draws the attention of mobile learning researchers.…”
Section: Related Workmentioning
confidence: 99%
“…As mobile technologies gain popularity among students, many studies have investigated the effectiveness of integrating these technologies into the learning activities. A study by van Rensburg et al (2022) reported the positive impact of using mobile technologies for learning in terms of increasing learning opportunities for students. Assessment as part of learning activities has become one of the domains that draws the attention of mobile learning researchers.…”
Section: Related Workmentioning
confidence: 99%